Is digital technology innovation a panacea for carbon reduction? - Pu, Zhengning; Qian, Yu; Liu, Ruiheng (Technological and Economic Development of Economy, 2025)
This paper analyses the impact of digital technological innovation on the carbon emission intensity of enterprises and conducts an empirical test based on the data of listed enterprises in China from 2009 to 2021. The study finds that (1) digital technological innovation can significantly reduce carbon emission intensity. (2) Enterprises’ digital attention and investment can significantly increase their operating income but not reduce carbon emissions. Digital technology patents can significantly reduce carbon emissions in the short term. In the long run, even new digital technologies will have a carbon rebound effect once they are deployed on a large scale. Therefore, digital technology innovation is still challenging in the long run to realize the synergy effect of “increasing production and reducing carbon.” (3) Mechanism tests show that digital technology innovation can reduce carbon intensity by improving operational efficiency, promoting cleaner production, and improving human capital. (4) If the government pays moderate attention to digital development, digital technological innovation by enterprises can significantly reduce carbon intensity. Meanwhile, this effect is more significant in regions with higher levels of intellectual property protection. Digital technology innovation can significantly reduce carbon intensity for mature, high-tech, and technology-intensive enterprises.First published online 18 November 2024